Exploring Opportunities for Promoting Synergies between Climate Change Adaptation and Mitigation in Forest Carbon Initiatives - Chia, E.L.; Fobissie, K.; Kanninen, M. (MDPI, 2016)
There is growing interest in designing and implementing climate change mitigation and adaptation (M + A) in synergy in the forest and land use sectors. However, there is limited knowledge on how the planning and promotion of synergies between M + A can be operationalized in the current efforts to mitigate climate change through forest carbon. This paper contributes to fill this knowledge gap by exploring ways of planning and promoting M + A synergy outcomes in forest carbon initiatives. It examines eight guidelines that are widely used in designing and implementing forest carbon initiatives. Four guiding principles with a number of criteria that are relevant for planning synergy outcomes in forest carbon activities are proposed. The guidelines for developing forest carbon initiatives need to demonstrate that (1) the health of forest ecosystems is maintained or enhanced; (2) the adaptive capacity of forest-dependent communities is ensured; (3) carbon and adaptation benefits are monitored and verified; and (4) adaptation outcomes are anticipated and planned in forest carbon initiatives. The forest carbon project development guidelines can encourage the integration of adaptation in forest carbon initiatives. However, their current efforts guiding projects and programs to deliver biodiversity and environmental benefits, ecosystem services, and socioeconomic benefits are not considered explicitly as efforts towards enhancing adaptation. An approach for incentivizing and motivating project developers, guideline setters, and offset buyers is imperative in order to enable existing guidelines to make clear contributions to adaptation goals. We highlight and discuss potential ways of incentivizing and motivating the explicit planning and promotion of adaptation outcomes in forest carbon initiatives.